Pengaruh Metode Pembelajaran Role Playing Terhadap Motivasi Belajar Pada Mata Pelajaran Ski Kelas VIII di MTS Al-Washliyah Sorkam - Dewi, Cantika Rafika; C, Charles (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Problems with class VIII MTs Al-Washliyah Sorkam, namely the dearth of instructional strategies that deter students from learning SKI, served as the impetus for this study. Due to the traditional method's lack of instructor involvement and inability to grab students' attention, pupils become less engaged, focused, drowsy, and lethargic. Researchers attempt to address this by using instructional strategies that boost students' enthusiasm to study. The technique is role-playing. The study question is whether the Al-Ayyubid Dynasty, which is the topic of class VIII, influences students' desire to learn while using the role-playing approach. The purpose of this study is to ascertain how the role-playing method's application affects class VIII students' desire to learn about the Al-Ayyubid Dynasty. With a static group comparison design, this study is experimental. Data collection for this study involves the use of documentation and questionnaires. The questionnaire was changed in accordance with the validator's recommendations after being verified by them. To ascertain if the role-playing approach has an impact on students' desire to study, a T-test is used to evaluate whether the hypothesis is accepted or rejected. The questionnaire t-test yielded a significant result based on the conducted investigation. At the 5% significance level, (2-tailed) = 0.000 < 0.05, rejecting Ho and accepting Ha. It is clear from the data that the role-playing learning approach at MTs Al-Washliyah Sorkam has a big impact on students' enthusiasm for study. Furthermore, according to the Tcount value of 14,727 > Ttable 1,666. Thus, based on tcount, there is a considerable effect, indicating that Ho is rejected and Ha is accepted.